Taxonomy of Litoria graminea (Anura: Hylidae), with descriptions of two closely related new species - Kraus, Fred (Zootaxa, 2018)
I clarify the correct provenance and taxonomic identity of the poorly known canopy-dwelling frog, Litoria graminea, from New Guinea. I base my redescription upon analysis of relevant historical material as well as upon more recently obtained specimens from several localities in Papua New Guinea. Determining the correct identity of L. graminea makes clear that one recently named species (L. dux Richards & Oliver) is a junior synonym of that taxon and that additional close relatives of that species remain undescribed, two of which I describe here. The first is known from a series of localities along the southern versant of the Central Dividing Range and the Owen Stanley Mountains. The second is known from a single site in the foothills of the Owen Stanley Mountains in Central Province, Papua New Guinea. Differences among the species are largely confined to pigmentation features and the shape of the male nuptial pads. Further, I show that several morphometric and color-pattern features earlier thought to distinguish among members of this complex are encompassed by natural variation within true L. graminea, making the characters taxonomically uninformative. The two newly described species share the unusual feature of having green oral mucosa, although their bones were white in life. This coloration is presumably due to sequestration of biliverdin, as seen in a few other tropical treefrogs, but the function of this sequestration remains unknown.